CaRo 2.0: An Interactive System for Expressive Music Rendering - Sergio Canazza; Giovanni De Poli; Antonio Rodà (Advances in Human-Computer Interaction)
In several application contexts in multimedia field (educational, extreme gaming), the interaction with the user requests that system is able to render music in expressive way. The expressiveness is the added value of a performance and is part of the reason that music is interesting to listen. Understanding and modeling expressive content communication is important for many engineering applications in information technology (e.g., Music Information Retrieval, as well as several applications in the affective computing field). In this paper, we present an original approach to modify the expressive content of a performance in a gradual way, applying a smooth morphing among performances with different expressive content in order to adapt the audio expressive character to the user’s desires. The system won the final stage of Rencon 2011. This performance RENdering CONtest is a research project that organizes contests for computer systems generating expressive musical performances.